Vitamin D level is associated with rupture of intracranial aneurysm in patients with subarachnoid hemorrhage - Wei, Sen; Yuan, Xin; Li, Dongdong; Fan, Feng; Guo, Xinbin; Xu, Yuming; Guan, Sheng (Frontiers in Neurology, 2022)
Background: Increasing evidence supports the relationship between vitamin D levels and stroke. However, there are few studies on the association between vitamin D levels and subarachnoid hemorrhage (SAH), especially in patients with aneurysmal SAH. The present study investigated the association between vitamin D level and rupture of intracranial aneurysm in a cohort of patients with SAH. Methods: The data of patients diagnosed with SAH at our hospital between September 2019 and December 2020 were retrospectively reviewed. Patients’ information was collected, and serum vitamin D levels were measured. Computed tomography was performed to confirm SAH diagnosis, and digital subtraction angiography was performed to determine whether SAH was caused by rupture of an intracranial aneurysm. Multivariate logistic regression analyses were performed to investigate the association between vitamin D level and aneurysmal SAH. Results: Overall, 193 patients with SAH were evaluated; 160 with aneurysmal SAH (age 55.86 ± 12.30 years, 63.15% female) and 33 with non-aneurysmal SAH (age 56.21 ± 9.92 years, 45.45% female). Univariate analysis showed that the vitamin D level in aneurysmal SAH was lower than that in non-aneurysmal SAH (16.95 ± 8.69 vs. 22.74 ± 9.12,ng/ml p=0.001). In addition, there were more patients with hypertension in aneurysmal SAH group than in non-aneurysmal SAH group (53.75% vs. 24.24%, p = 0.002). Notably, there was still a strong correlation between vitamin D level and aneurysmal SAH after adjusting for confounders in the multivariate model (odds ratio, 0.935; 95% confidence interval, 0.890–0.983; p = 0.008). Conclusion: Vitamin D level is associated with rupture of intracranial aneurysm in patients with SAH. Patients with aneurysmal SAH have lower vitamin D levels than those with non-aneurysmal SAH.